Language and Gender: Differences in the Language of Women and Men in “A Business Proposal” K-Drama - Purnami, Anak Agung Istri Agung Tri; Laksminy, Luh Putu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Sociolinguistics is a field within linguistics that collaborates with sociology, focusing on the interplay between language and social elements within a community of speakers. This particular study aims to explore the linguistic differences between women and men. The research is titled "Language and Gender: Analyzing Variances in the Speech of Women and Men in the K-Drama ’A Business Proposal’." The chosen research methods are surveys and observational techniques, aligned with the indirect observation suggested by the study title. The data collection is grounded in Lakoff’s theory. The selection of "A Business Proposal" as the subject of analysis is motivated by its popularity among fans since its release in 2022. Additionally, the K-Drama is considered relatable for young audiences, particularly in the realm of romance. The storyline is straightforward and easily comprehensible for viewers. The research revolves around the theme of Language and Gender, with the data extracted from the K-Drama shedding light on the lives of four main characters: Shin Ha Ri, Kang Tae Mu, Jin Young So, and Cha Sung Hoon.